EFEKTIVITAS DUKUNGAN KELUARGA DALAM PELAKSANAAN SELF MANAGEMENT DIABETES MELITUS TIPE 2 BERDASARKAN HEALTH BELIEF MODEL : SYSTEMATIC REVIEW - Yaumil Hafsani Siregar (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Diabetes Mellitus Type 2 is insulin resistance which influenced by lifestyle factors and obesity that requires intervention, one of which is health education based on health belief model. Health education self-management based on health belief mode lis the right management requires the role of health workers including nurses and families in order to improve quality of life Type 2 Diabetes Mellitus patients. Systematic Review aims to identify the effectiveness of family support in implementing self-management Diabetes mellitus based onhealth belief model. Article search using database: PubMed, Science Direct and Google Scholar with inclusion criteria, namely: full text, in the range 2014-2021 , having DOI, the type of Randomized Control Trials (RCT) research selected using JBI assessment. From the literature search, 7 articles were obtained that met the criteria for the study. The seven articles state that family support in doing self-management based on health belief model effective for controlling HbA1c, blood sugar levels, reducing stress, promoting a healthy lifestyle, coping, and health domains of quality of life. Family support in self-management based onhealth belief model can improve the quality of life of Type 2 Diabetes Mellitus patients. So it is necessary to have an intervention program based on family support in collaboration with nurses to improve self-management compliance by adjusting the health conditions of Type 2 Diabetes Mellitus patients.